Writing Composition Problem in Arabic Language Learning Among Arabic Language Education Students - Zulaeha Zulaeha (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
Learning foreign languages, especially Arabic, is still an obstacle for non-Arabic speakers. Apart from the problem of grammatical gaps, and phonological differences between source and target languages, writing composition proficiency is also a problem in learning arabic that often occurs, especially among Arabic language learners in higher education. Anchored by this problem, this study aims to investigate errors in the practice of arabic sentences composition made by learners at the university level, as well as the factors behind it. To explain this problem, the Error Foreign Language (EFL) approach to the content of insyā’ (writing/composing) assignments written by students in Arabic courses are involved as an analytical framework. The results of the analysis reveal that the types of tarkīb errors that appear in students’ assignments include; First, errors in the use of the letters jār, tarkib iḍāfī, tarkīb waṣfī, tarkīb jumlah fi’liyah, and tarkīb jumlah ismiyah that consist of mubtada’ (subject of the sentence) with khabar jumlah fi’ilyah, and mubtada’ with khabar mufrad. The factors that cause this are the result of interlingual interferences, inadequate learning, simplification, and fault analogy in Arabic language rules. The implications and recommendations for this problem are described intensely at the end of this study.